O PIBID como política articuladora na construção de currículos críticos: o trabalho desenvolvido no Instituto Federal Farroupilha – Campus São Vicente do Sul - Paniz, Catiane Mazocco (2017)
The curriculum in Science Education, many times, is still disciplined and fragmented, not generating problematization and dialogue. This view has already been critically discussed by several authors who defend the implementation of critical curricula, built from the problematization of the reality experienced by the subject. However, to be feasible the implementation of these, it is also essential to reflect on the initial and permanent training of educators. This needs to be legitimized as a process in which educators are autonomous subjects and not mere curricula players. A public policy that can assist in this training is the Institutional Program of Initiation to Teaching Scholarship (Pibid). In this context, this study emerges, which has as a research problem: the Pibid, as public policy, assists in structuring of formative processes for the preparation, implementation and reflection of curriculum from the perspective of the three Pedagogical Moments (3PM). In what way? From the research problem, the objectives of the work are focused on: developing a formative process in a collective and interdisciplinary way with regent teachers and scholars of Biology and Chemistry Pibid, with the reflection and the construction of the curriculum, from the use of 3PM; explaining how the generator themes were found from the Study of the Reality; and analyze if the formative process performed in the Pibid enables the elaboration, the implementation and the reflection of curricula based on 3PM. The survey subjects were scholars and Pibid supervisors of the major course in biological Sciences and the major course in Chemistry of Instituto Federal Farroupilha-campus São Vicente do Sul. To answer to the goals, initially, it was implemented a training process with scholars and supervisors of the Pibid, aiming to provide the reflection on the curriculum, the interdisciplinary, the Thematic Approach and on the Three Pedagogical Moments (3PM), as curricula structuring. On this basis, plans were drawn up by the participants of the training process, instruments for the realization of the Study of Reality (SR) to get to the Generator Themes. With the Generator Themes defined, the plans have been developed for implementation in four interdisciplinary partner schools of Pibid. For the analysis of the results, it was used the Discursive Textual Analysis (DTA) and the following categories emerged from the process: the Restructuring of the Curriculum from the work with the Generator Themes, the Collective and Interdisciplinary Work, the Dialogue as a way to allow the Questioning of Reality and a New Look to the School and to the Institution of Higher Education. Among the main results are highlighted: the importance of the Pibid on the change of vision in relation to the curriculum, recognizing the educators as subjects capable of thinking collectively, developing and implementing curricular practices that starts from the questioning of reality; the importance of interdisciplinary work, dialogic and shared; and the importance of seeing the Basic Education school as a space for knowledge construction, able to think formative processes in conjunction with Higher Education Institutions.